Preservation of Gasing Game as Cultural Identity in Pematang Lumut Village, Jambi Province: Pelestarian Permainan Gasing Sebagai Identitas Budaya di Desa Pematang Lumut Provinsi Jambi - Hendra Gunawan; Irmawati Sagala; Aldi Saputra Utama (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The Gasing game in Pematang Lumut Village is a traditional game that has become their cultural identity, but in its development, it has been displaced by modern digital-based games. The Gasing Game Assistance Activity in Pematang Lumut Village is a community service activity carried out by Lecturers and Students of UIN Sulthan Thaha Saifuddin Jambi to increase the existence of the top game as a cultural identity. This activity done by using the Participatory Action Research (PAR) approach, researchers collaborated with the Pematang Lumut Village community to assist the young generation in playing tops. The activities include socialization of the importance of preserving traditional games, the introduction of Gasing tops and how to play the Gasing, as well as preservation through holding competitions that will be made a routine village agenda. The success of the mentoring is measured by the impact it produces, such as the number of competition participants and the enthusiasm of the community in participating in the top game mentoring. The Pematang Lumut Village also plans to make the spinning top competition an annual agenda so that the cultural identity of Pematang Lumut Village is maintained.